Cytogenetic, hybridization and molecular evidence of four cytological forms of Anopheles nigerrimus (Hyrcanus Group) in Thailand and Cambodia - Songsawatkiat S. (2014)
Thirteen isoline colonies of Anopheles nigerrimus were established from individual wild-caught females collected from cow-baited traps at locations in Thailand and Cambodia. Three types of X (X1, X2, X3) and 4 types of Y (Y1, Y2, Y3, Y4) chromosomes were recovered, according to differing amounts of extra heterochromatin. Four karyotypic forms were designed depending upon apparently distinct figures of X and Y chromosomes, i.e., Form A (X1, X2, X3, Y1), B (X2, X3, Y2), C (X1, Y3), and D (X3, Y4). Forms C and D were new metaphase karyotypes discovered in this study. Form A appeared to be common in both Thailand and Cambodia. Forms B and D were found to be rather specific to southern and northeastern Thailand, respectively, whereas Form C was confined to Cambodia. Hybridization experiments among the eight isoline colonies, which were representative of four karyotypic forms of An. nigerrimus, demonstrated genetic compatibility in giving viable progenies and synaptic salivary gland polytene chromosomes through F2-generations. These results elucidated the conspecific relationship, comprising four cytological forms within this taxon. Supportive evidence was confirmed further by very low intraspecific sequence variations (average genetic distance = 0.002-0.007) of the nucleotide sequences in ribosomal DNA [second internal transcribed spacer (ITS2)] and mitochondrial DNA [cytochrome c oxidase subunit I (COI) and subunit II (COII)]. © 2013 The Society for Vector Ecology.